Nightmare on eck street - Cox, Michael; Smedley, Chris (Hodder Children's London, 2002)
Can Claire and Jason stop the vampire invasion before it grips the world? They'll need to be careful and cunning, alert and aware. They'll need to vigilant. They'll be vampire vigilantes.